Research on Manufacturing Technology of Super-large Module Climbing Pinions - Ren Ning; Zhou Feng (Jixie chuandong)
The climbing pinion is an important part of the jacking system of a self-elevating platform and the manufacturing of super-large module climbing pinions belongs to the extreme processing requiring high manufacturing technology. Rough tooth processing, heat treatment process test and finished tooth processing are the key technologies in manufacturing super-large module climbing pinions. The improved oxygen-gas NC flame cutting technology is used for rough teeth, which can make the tooth flank and tooth root after quenching and tempering treatment obtain surface hardness above 330 HB. To study the mechanical properties of climbing pinions after quenching and tempering treatment, the material performance test is performed on the specimens taken from climbing pinion forgings, and the results show that the tensile property and impact energy of the materials meet the mechanical property requirements. NC milling technology is used to process finished teeth of climbing pinions, and the results show that the roughness of tooth surface of climbing pinions can be controlled within Ra=6.3 μm, and the deviation of common normal length can be controlled within 0.2 mm. The manufacturing process and control measures of the above key links ensure that the finished product quality of climbing pinions can meet the technical requirements.